Acoustic measurements on monolithic aerogel samples and application of the selected solutions to standard window systems. (15th December 2018) - Merli, Francesca; Anderson, Ann M.; Carroll, Mary K.; Buratti, Cinzia
Abstract: Silica aerogels are thermally and acoustically insulating and can offer advantages in building thermal applications. They come in granular (multiple small pieces) and monolithic (single piece) form. Granular aerogels are relatively easy to produce and can be incorporated into large window systems. Large monolithic aerogels are more difficult to produce, but they offer superior optical and thermal performance. The aim of this paper is to experimentally investigate the acoustic properties of monolithic aerogel samples fabricated using a rapid supercritical extraction method. The acoustic absorption coefficient (α) and the transmission loss (TL) were measured at normal incidence in a traditional impedance tube in the 100–5000 Hz frequency range, for three thicknesses, from 12.7 to 25.4 mm. Good acoustic performance was achieved: 12.7-mm-thick cylindrical monoliths have a peak acoustic absorption coefficient of 0.88 at ∼1500 Hz. When the thickness increases, α decreases (to 0.78 and 0.54 for 19-mm and 25.4-mm thick samples, respectively), with peaks at lower frequencies (1300 and 1100 Hz). The transmission loss increases with aerogel thickness with values as high as 10–15 dB in the 100- to 1600-Hz range. When compared to granular aerogels, the monoliths have TLs that are 5–7 dB larger in the 100- to 1600-Hz range. To further compare performance, small glazing packages were fabricated from glass panels with air, granular, or monolithic aerogel in the interspace. The TL was evaluated and found to be in the 35- to 45-dB range for all samples. The monolithic aerogel glazing had the highest TL, particularly in the 200- to 1000-Hz range. Based on these results, we estimated a 3-dB increase in the sound insulation index for the glazing system with a monolith when compared to the glazing system with air, and a 1- to 2-dB increase when compared to the granular aerogel glazing. This study demonstrates that the use of transparent monolithic silica aerogel in the interspace of conventional glazing systems would result in significant improvement in noise insulation.